Gaseous emission comparison of a compression-ignition engine fueled with different biodiesels - Altun, S.; Oner, C. (Springer, 2013)
In this study, it was performed a comparison of the performance and emissions of two methyl ester fuels: one obtained from animal fat and the other from crude canola oil, in a compression-ignition engine against diesel fuel. The experimental results compared with diesel fuel showed that significant reductions could be obtained by biodiesel derived from animal fat in carbon monoxide and oxides of nitrogen emissions. Carbon dioxide emissions showed a trend of decreasing with the biodiesel fuels. An increase in brake specific fuel consumption was observed for different biodiesel fuels when compared with diesel fuel. It was concluded that animal tallow methyl ester performed better than canola oil methyl ester, whereas slightly higher brake torque is observed with canola oil methyl ester.
Keywords: Air pollution; Diesel; Performance